1983
DOI: 10.1136/jmg.20.6.473
|View full text |Cite
|
Sign up to set email alerts
|

De novo interstitial direct duplication of 15q: 46,XY,dir dup(15) (pter leads to q24::q14 leads to q21 X 1::q24 leads to qter).

Abstract: SUMMARY A profoundly retarded, slightly dys-Case report morphic male was re-examined cytogenetically The patient by high resolution GTG banding and found to Caucasian r have a de novo interstitial direct duplication of of a 34-yea 1 5q. 36-year-old

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
10
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 2 publications
2
10
0
Order By: Relevance
“…However, most of these had distal breakpoints and the monosomic material most likely contributed minimally to the phenotype. Only two cases involved a tandem duplication4 15 and one of these was in mosaic form 4. The other case was interstitial involving the region 15q14→q21.1, therefore overlapping only minimally with our case 15…”
supporting
confidence: 70%
“…However, most of these had distal breakpoints and the monosomic material most likely contributed minimally to the phenotype. Only two cases involved a tandem duplication4 15 and one of these was in mosaic form 4. The other case was interstitial involving the region 15q14→q21.1, therefore overlapping only minimally with our case 15…”
supporting
confidence: 70%
“…In contrast to the above cases, our patient has duplication of the mid-distal part of the long arm of chromosome 15. Herr et al [1983] reported a profoundly re- tarded, slightly abnormally appearing male with a direct interstitial duplication of 15(q14→q21.1) with duplicated segments, which overlap with those in our case. However, the patient also had skeletal problems and hypogonadism and in general appears to be more severely affected than our case.…”
Section: Discussionsupporting
confidence: 50%
“…The second chromosome involved in the reciprocal translocation has varied; chromosomes 2, 7, 8, 11, 13, 15 (Robertsonian translocation), and 21 have been reported [Fujimoto et al, 1974;Schnatterly et al, 1984;Goldstein et al, 1987;Lacro et al, 1987;Jalal et al, 1989;Van Allen et al, 1992]. Other cases of 15q duplication have been the result of direct or inverted duplication [Yip et al, 1982;Herr et al, 1983;Chandler et al, 1997;Elcioglu et al, 1997].…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Herr et al [1983] reported a 12-year-old boy with a de novo interstitial duplication of 15q14q21.1, who presented with scrotal hypoplasia and micropenis, short stature, seizure disorder, distinctive facial features, kyphosis and scoliosis, global developmental delay, and intellectual disability. Elçioglu et al [1997] described a patient with hypogonadism, dysmorphic facial features, hypotonia, developmental delay, Marfan-like features and intellectual disability, who carried a de novo interstitial inverted duplication involving bands 15q13.3q21.3.…”
Section: Discussionmentioning
confidence: 99%